Métodos diagnósticos para la evaluación de patologías cardiacas en perros (2024)
The diagnosis of heart diseases in the small animal clinic is usually a major challenge for the veterinarian. In many cases, he or she does not have the knowledge about the different diagnostic tools that allow the identification of these pathologies. In the clinic, the diagnosis of congenital or veterinary acquired heart disease begins with a clinical assessment and an electrocardiogram (ECG). In some patients, the study is expanded with stress testing, Doppler ultrasound, and cardiac magnetic resonance (CMR). They can be used to diagnose and evaluate cardiac pathologies, allowing early detection in some cases to establish appropriate treatment and management for the patient and guarantee quality of life.